Pentapartitioned Neutrosophic Pythagorean Resolvable and Irresolvable Spaces - R. Radha; A. Stanis Arul Mary; Said Broumi (Neutrosophic Sets and Systems, 2021)
In this paper, the concepts of Pentapartitioned Neutrosophic Pythagorean resolvable , Pentapartitioned Neutrosophic Pythagorean irresolvable, Pentapartitioned Neutrosophic Pythagorean open hereditarily irresolvable and maximally Pentapartitioned Neutrosophic Pythagorean irresolvable spaces are introduced. Also we investigated several properties of the Pentapartitioned Neutrosophic Pythagorean open hereditarily irresolvable spaces besides giving characterization of these spaces by means of somewhat Pentapartitioned Neutrosophic Pythagorean continuous functions and somewhat Pentapartitioned Neutrosophic Pythagorean open functions.